INTERNALISASI NILAI NILAI MULTIKULTURAL DALAM PENDIDIKAN TASAWUF DI PONDOK PESANTREN SUNAN KALIJOGO JABUNG - Sutiyo; Ahmad maruf (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
This research begins with phenomena that appear to be related to the internalization of multicultural values found in the Pondok Sunan Kalijogo Jabung environment. As it is known that the Sunan Kalijogo Jabung Islamic Boarding School has been committed to upholding the values of Sufism education, and has been used as the basis for the behavior of the pesantren. The approach in this study uses a qualitative approach to the type of phenomenological research. This research data collection uses three techniques, namely: (1) in-depth interviews (in-depth interviews); (2) participant observation (participant observation); and (3) study document (study document). For data analysis using descriptive techniques whose application is carried out in three activity lines, namely data reduction, data presentation, and drawing conclusions or verification. The data checking technique used in this research is triangulation technique. The multicultural values ​​applied in Sufism education at the Sunan Kalijogo Jabung Islamic Boarding School are the values ​​of tolerance, values ​​of democracy/freedom, values ​​of equality/equality, and values ​​of justice.